2018
DOI: 10.1177/2516043518796442
|View full text |Cite
|
Sign up to set email alerts
|

Measuring shared mental models in healthcare

Abstract: Objective: To review common qualitative and quantitative methods of measuring shared mental models appropriate for use in the healthcare setting. Background: Shared mental models are the overlap of individuals' set of knowledge and/or assumptions that act as the basis for understanding and decision making between individuals. Within healthcare, shared mental models facilitate effective teamwork and theorized to influence clinical decision making and performance. With the current rapid growth and expansion of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 64 publications
(127 reference statements)
0
12
0
Order By: Relevance
“…With observation alone we cannot directly estimate the extent that members share representations. In contrast, validated psychological measures of shared mental models often involve tools to identify critical aspects of teamwork in context, measure members’ individual perceptions of those aspects, and/or evaluate a group based on the degree to which members share representations [ 85 ]. Resuscitation researchers might adapt such tools to support both comprehensive evaluations of healthcare teams and specific measures of identified group processes and emergent states [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…With observation alone we cannot directly estimate the extent that members share representations. In contrast, validated psychological measures of shared mental models often involve tools to identify critical aspects of teamwork in context, measure members’ individual perceptions of those aspects, and/or evaluate a group based on the degree to which members share representations [ 85 ]. Resuscitation researchers might adapt such tools to support both comprehensive evaluations of healthcare teams and specific measures of identified group processes and emergent states [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest future research using shared mental model frameworks to determine how overlapping clinician knowledge and assumptions influence surgical clinical decision making and performance. 45 Interprofessional clinicians who regularly work together may form shared mental models that confer benefits in the surgical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity is theoretically linked to shared mental models in surgical settings, but there is no direct evidence to support these assumptions. Thus, we suggest future research using shared mental model frameworks to determine how overlapping clinician knowledge and assumptions influence surgical clinical decision making and performance 45 …”
Section: Discussionmentioning
confidence: 99%
“…The lack of an adequate SMM in teams have been often been related to the occurrence of team errors [9,17]. It is suggested that SSM play a major role in the effectiveness, efficiency of the group decision process and performance in a variety of domains, e.g., aviation decision making and medical team decision making and command and control [3,12,14,19,25,[37][38]. Among others the adequacy of SSM have been related to patent safety in the operation room, e.g., open heart operation and tracheal intubation [15,23].…”
Section: Shared Mental Modelsmentioning
confidence: 99%